PENGARUH PERMAINAN NUMBER DOOR TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 5-6 TAHUN DI TK PEMBINA KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - Fitriani, Sy; Chairilsyah, Daviq; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect ogame of number door toward the ability to know the concept of numbers of children aged 5-6 years at pembina kindergarten in sub district of mandah district of indragiri hilir. The method of this research userd experimentalmethod with using one group pre-test post-test design. The samples used in this study were 25 students. The data collection technique used is observasion. Technique of data analysis used t-test by using program of spss 16. The research hypothesis was to find the effect ogame of number door toward the ability to know the concept of numbers of children aged 5-6 years at pembina kindergarten in sub district of mandah district of indragiri hilir. Based on data analysis was known that thitung= 17,137> ttabel = 2.064 Sig. (2-tailed) = 0,000. Because sig< 0,05 it can be concluded that there is difference of ability to know the concept of numbers that was be done before and after of number door .it can be interpreted that there is effect of game of number door activity toward the ability to know the concept of numbers of children aged 5-6 years in sub district of mandah district of indragiri hilir significant that is equal to 51,34%.Keyword: The ability to know the concept of numbers, Game